2015
DOI: 10.1155/2015/538246
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Level of the Primary Healthcare Providers on Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilitation

Abstract: Introduction. Awareness of the healthcare providers on chronic obstructive pulmonary disease (COPD), which is an important cause of mortality and morbidity in our country and all over the world, and on pulmonary rehabilitation (PR) which plays an important role in its nonpharmacological treatment will provide effectiveness in diagnosis and treatment of COPD. The present study aimed at determining knowledge level of the healthcare providers about COPD and PR. Materials and Methods. In this cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…In addition to gaps in knowledge and skills, Ugandan primary care is hampered by lack of continuity in the diagnosing of chronic respiratory problems as well as by lack of skills building of technological diagnostic procedures. Studies from other countries have also shown gaps in knowledge and skills among primary care clinicians for managing patients presenting with chronic respiratory symptoms [32]. For example , Yawn, et al 2008 found that primary care physicians, Nurse Practitioners (NPs), and Physician Assistants (PAs) working in some parts of the US lacked awareness of COPD guidelines [33], and a similar problem was detected in the UK amongst practice nurses many of whom lacked confidence and training [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gaps in knowledge and skills, Ugandan primary care is hampered by lack of continuity in the diagnosing of chronic respiratory problems as well as by lack of skills building of technological diagnostic procedures. Studies from other countries have also shown gaps in knowledge and skills among primary care clinicians for managing patients presenting with chronic respiratory symptoms [32]. For example , Yawn, et al 2008 found that primary care physicians, Nurse Practitioners (NPs), and Physician Assistants (PAs) working in some parts of the US lacked awareness of COPD guidelines [33], and a similar problem was detected in the UK amongst practice nurses many of whom lacked confidence and training [34].…”
Section: Discussionmentioning
confidence: 99%
“…Education and training programs are recommended even for pulmonologists in recent guidelines [33]. In a study conducted in Turkey, primary healthcare providers such as family practitioners and homecare staff were found to have inadequate information about COPD and PR [34]. In a Turkish survey study, it was reported that the levels of knowledge of chest physicians about PR was substantially in the range of low to moderate in a small city of Turkey [35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other countries have also shown gaps in knowledge and skills among primary care clinicians for managing patients presenting with chronic respiratory symptoms [32]. For example, Yawn, et al 2008 found that primary care physicians, Nurse Practitioners (NPs), and Physician Assistants (PAs) working in some parts of the US lacked awareness of COPD guidelines [33], and a similar problem was detected in the UK amongst practice nurses many of whom lacked confidence and training [34].…”
Section: Discussionmentioning
confidence: 99%